Qualitative Investigation of the Singular Cauchy Problem _k = 1^n (a_k1 t + a_k2 x)(x’)^k = b_1 t + b_2 x + f(t,x,x’),x(0) = 0 - Zernov, A. E. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We prove the existence of continuously differentiable solutions x:(0,ρ] → R with required asymptotic properties as t → +0 and determine the number of these solutions.